A Meta-Analysis of the Ultimate Effect of Mesenchymal Stem / Stromal Cell in Tumor Animal Models - Pratika Yuhyi Hernanda (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Several studies have reported the Mesenchymal Stem Cell (MSC) triggered and inhibited tumor growth. We therefore performed a systematic review and meta-analysis of experimental studies evaluating the effects of MSC on tumors. Method: We collected the relevant studies by searching ProQuest, PubMed Publisher, and GoogleScholar. A meta-analysis was performed for the outcome measure: tumor volume and tumor weight. The search resulted in 440 references, of which 22 could be included in the meta-analysis. Of these 22 experiments, 18 (40%) showed a significant decrease of tumor growth and 27 (60%) experiments showed a significant increase of tumor growth. The engineered MSC and the late phase of MSC injection have a significant contribution to tumor inhibition effect. The meta-analysis showed that there are no significant effect of mesenchymal stem cell therapy to the tumor animal volume (SMD-0.23[-0.55, 0.09]; n=15), and to the tumor animal weight (SMD -0.19 [-0.77,0.39]; n=7). Conclusion: MSC appears to have a relative dependent effect in animal models.